Elevated TRPV4 Levels Contribute to Endothelial Damage and Scarring in Experimental Spinal Cord Injury - Kumar, Hemant (J Neurosci, 2020)
Currently, the role of transient receptor potential vanilloid type 4 (TRPV4), a nonselective cation channel in the pathology of spinal cord injury (SCI), is not recognized. Herein, we report the expression and contribution of TRPV4 in the pathology of scarring and endothelial and secondary damage after SCI. TRPV4 expression increased during the inflammatory phase in female rats after SCI and was expressed primarily by cells at endothelial-microglial junctions. Two-photon microscopy of intracellular-free Ca(2+) levels revealed a biphasic increase at similar time points after SCI. Expression of TRPV4 at the injury epicenter, but not intracellular-free Ca(2+), progressively increases with the severity of the injury. Activation of TRPV4 with specific agonist altered the organization of endothelial cells, affected tight junctions in the hCMEC/D3 BBB cell line in vitro, and increases the scarring in rat spinal cord as well as induced endothelial damage. By contrast, suppression of TRPV4 with a specific antagonist or in female Trpv4 KO mouse attenuated inflammatory cytokines and chemokines, prevented the degradation of tight junction proteins, and preserve blood–spinal cord barrier integrity, thereby attenuate the scarring after SCI. Likewise, secondary damage was reduced, and behavioral outcomes were improved in Trpv4 KO mice after SCI. These results suggest that increased TRPV4 expression disrupts endothelial cell organization during the early inflammatory phase of SCI, resulting in tissue damage, vascular destabilization, blood–spinal cord barrier breakdown, and scarring. Thus, TRPV4 inhibition/knockdown represents a promising therapeutic strategy to stabilize/protect endothelial cells, attenuate nociception and secondary damage, and reduce scarring after SCI. SIGNIFICANCE STATEMENT TRPV4, a calcium-permeable nonselective cation channel, is widely expressed in both excitable and nonexcitable cells. Spinal cord injury (SCI) majorly caused by trauma/accidents is associated with changes in osmolarity, mechanical injury, and shear stress. After SCI, TRPV4 was increased and were found to be linked with the severity of injury at the epicenter at the time points that were reported to be critical for repair/treatment. Activation of TRPV4 was damaging to endothelial cells that form the blood–spinal cord barrier and thus contributes to scarring (glial and fibrotic). Importantly, inhibition/knockdown of TRPV4 prevented these effects. Thus, the manipulation of TRPV4 signaling might lead to new therapeutic strategies or combinatorial therapies to protect endothelial cells and enhance repair after SCI.